Pemahaman Iman Kristen Terhadap Kedatangan Anti Kristus Berdasarkan 1 Yohanes 4:1-6 - Olohesi Warae; Abad Jaya Zega (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
in general from the first century to date, has a lot of deviant teaching from the Bible. Teaching that deviates and is able to shaken the faith of Christians, this can happen if Christians do not hold fast to their faith that he believes in Jesus Christ as the Savior, the research method carried out is a description that can sought how Christians understand the arrival Antichrist and how to reactly perverts, namely first: test the Spirit; Second: Know the Spirit of God and third: know the status of the Son of God.